MINAT BELAJAR DI MASA PANDEMI COVID – 19 DALAM HUBUNGANNYA DENGAN HASIL BELAJAR KELAS IV - Desi Meliana; Budiman Tampubolon; Hery Kresnadi (Universitas Tanjungpura, 2022)
AbstrakThis study aims to describe Students' Interest in Learning During the Covid-19 Pandemic in Relation to Learning Outcomes in Class IV Thematic Learning at Kartika XVII-1 Elementary School Pontianak. The method used is a descriptive method in the form of relationship studies (interrelationship studies) using a correlation study research method (correlation studies). This research is a population study with a total of 25 students. Data collection techniques in this study are interview techniques, questionnaires (questionnaire) and document collection. The data collection tools used are questionnaires and documents on the average value of students' daily tests. The results showed that 83.20% of students' interest in thematic learning during the Covid-19 pandemic at Kartika XVII-1 Pontianak Elementary School was 83.20% in the